Kelayakan booklet materi metabolisme di kelas XII - Ruqiah Ganda Putri Panjaitan; Ayu Kartika; Eko Sri Wahyuni (IKIP PGRI Pontianak, 2021)
This research aimed to determine booklet media advisability on metabolism material for student grade XII. Booklet media arranging based on kratom leaves protection power test to the pancreatic organ of mice that consumed alcoholic beverages. The methods used in this study was descriptive. This research was carried out through two stages, arrange metabolism material and the result of kratom leaves protection power test to the pancreatic organ of mice that consumed alcoholic beverages into booklet media and validated that media until valid to use as learning media. Validation of the media was validated by 5 validators. As for the aspect assessed covering aspects of format, content, and language. Data were analyzed by CVR and CVI formulas using the lawshe method. The result of instrument validation showed that the instrument sheet was suitable for use and repaired whole the booklet media obtained CVR and CVI values of 0.99 in accordance with the minimum value of the lawshe so that it was declared valid and feasible to be used as a learning medium on metabolism material for student grade XII.